Accuracy of serological testing for SARS‐CoV‐2 antibodies: First results of a large mixed‐method evaluation study. Issue 3 (13th November 2020) - Brigger, Daniel; Horn, Michael P.; Pennington, Luke F.; Powell, Abigail E.; Siegrist, Denise; Weber, Benjamin; Engler, Olivier; Piezzi, Vanja; Damonti, Lauro; Iseli, Patricia; Hauser, Christoph; Froehlich, Tanja K.; et al.
Abstract: Background: Serological immunoassays that can identify protective immunity against SARS‐CoV‐2 are needed to adapt quarantine measures, assess vaccination responses, and evaluate donor plasma. To date, however, the utility of such immunoassays remains unclear. In a mixed‐design evaluation study, we compared the diagnostic accuracy of serological immunoassays that are based on various SARS‐CoV‐2 proteins and assessed the neutralizing activity of antibodies in patient sera. Methods: Consecutive patients admitted with confirmed SARS‐CoV‐2 infection were prospectively followed alongside medical staff and biobank samples from winter 2018/2019. An in‐house enzyme‐linked immunosorbent assay utilizing recombinant receptor‐binding domain (RBD) of the SARS‐CoV‐2 spike protein was developed and compared to three commercially available enzyme‐linked immunosorbent assays (ELISAs) targeting the nucleoprotein (N), the S1 domain of the spike protein (S1), and a lateral flow immunoassay (LFI) based on full‐length spike protein. Neutralization assays with live SARS‐CoV‐2 were performed. Results: One thousand four hundred and seventy‐seven individuals were included comprising 112 SARS‐CoV‐2 positives (defined as a positive real‐time PCR result; prevalence 7.6%). IgG seroconversion occurred between day 0 and day 21. While the ELISAs showed sensitivities of 88.4% for RBD, 89.3% for S1, and 72.9% for N protein, the specificity was above 94% for all tests. Out of 54 SARS‐CoV‐2 positive individuals, 96.3% showed full neutralization of live SARS‐CoV‐2 at serum dilutions ≥ 1:16, while none of the 6 SARS‐CoV‐2‐negative sera revealed neutralizing activity. Conclusions: ELISAs targeting RBD and S1 protein of SARS‐CoV‐2 are promising immunoassays which shall be further evaluated in studies verifying diagnostic accuracy and protective immunity against SARS‐CoV‐2. Abstract : 1477 individuals are tested with 4 different serological SARS‐CoV‐2 immunoassays. ELISA against S1, RBD and N show superior accuracy compared to LFI against S. 96.4% of patient sera that are positive in ELISA show full neutralization of live SARS‐CoV‐2. Abbreviations: ELISA, enzyme‐linked immunosorbent assay; LFI, lateral flow immunoassay; S1, S1 domain of the spike protein; S, spike protein; sens, sensitivity; spec, specificity; RBD, receptor‐binding domain of the spike protein; N, nucleocapsid protein.